Engagement of people with disabilities in leisure activities: an occupational therapeutic perspective (Research, Society and Development, 2023)
Introduction: The practice of leisure provides relaxation, fun, socialization, important aspects for a person's health. For the physically challenged, leisure offers the same benefits, but the engagement in this activity differs from a typical person. In view of this, barriers and negative experiences are faced by the physically disabled public, which make it difficult to carry out leisure. Objective: To analyze the engagement promoted by people with physical disabilities when practicing leisure activities. Methodology: A systematic literature review was carried out in the Scopus database and in the Journals Database of the Coordination for the Improvement of Higher Education Personnel (Capes), in the last five years, with the following descriptors: "physical disabled" AND "leisure activities" ; Physical disabled" AND "recreation"; "Sports for persons with disabilities" AND "leisure activities". Results: 56 articles were found in Scopus and 782 articles in capes, in total, 138 articles related to the descriptors were located, from the analyzes carried out , promising data on barriers and lack of accessibility in leisure activities are identified, however, there is a lack of articles that relate Occupational Therapy and the leisure context of people with physical disabilities. Conclusion: Leisure is considered an essential occupation for the routine of individuals. However, people with disabilities (PCDs) may encounter many barriers to engaging in this occupation. It is worth mentioning that the Occupational Therapy (OT) professional is qualified to intervene with this public, since they are people with physical limitations who find it difficult to perform an occupation that is everyone's right.